2012
DOI: 10.1107/s0909049512049114
|View full text |Cite
|
Sign up to set email alerts
|

A survey of global radiation damage to 15 different protein crystal types at room temperature: a new decay model

Abstract: A systematic study of the sensitivity to radiation damage of crystals held at room temperature for a large set of model macromolecular structures is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 63 publications
8
54
0
Order By: Relevance
“…The collection of diffraction data continuously and at dose rates in excess of $0.7 MGy s À1 allowed more data to be collected from each crystal. In contrast, other recent studies (for example, Warkentin et al, 2013;Leal et al, 2013) conducted at lower dose rates have reported little dose-rate dependence at room temperature.…”
Section: Introductionmentioning
confidence: 65%
“…The collection of diffraction data continuously and at dose rates in excess of $0.7 MGy s À1 allowed more data to be collected from each crystal. In contrast, other recent studies (for example, Warkentin et al, 2013;Leal et al, 2013) conducted at lower dose rates have reported little dose-rate dependence at room temperature.…”
Section: Introductionmentioning
confidence: 65%
“…We advise that the 0.38-MGy dose limit not be exceeded when global damage is to be minimized. This dose limit holds strictly true only for tetragonal HEWL crystals at 2-Å resolution, but RT studies on other protein crystals (see above) reported D 1/2 values of the same order of magnitude ranging from 0.10 to 1.18 MGy at various resolutions and employing a variety of techniques to estimate the dose (20,23,26,32,34,35,60).…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite to optimizing the experimental protocol is knowing the effective crystal lifetime available for data collection. Diffracted intensity is known to decay with dose (6,7), relative B factor B rel is known to increase (8), and protocols exist for determining dose tolerance under carefully controlled conditions (9). However, when collecting data with the goal of solving challenging new structures, these results are often of limited use (10), because the optimally efficient even-dose case (11) is often not experimentally achievable.…”
mentioning
confidence: 99%